PREDICTION OF FATIGUE LIFE OF AUTOMOTIVE ALUMINUM LOWER SUSPENSION ARM (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
The objective of this study is to evaluate the potential of light alloy use in automobile parts by studying their fatigue life using various parameters such as the effect of the suspension, the nature of the excitation, thegeometry and the weight of the part. The part under study is the lower suspension arm made of 7075-T6 aluminium alloy. The energy approach enables us to compare two of the same order of tensors, the multiaxial andthe uniaxial cases. In both cases, the strain energy density is a zero tensor order. The random displacement excitation is obtained analytically from the power spectral density PSD. The force excitation is obtained by a simple normalisation of spectrum displacement. To avoid the use of the Newton-Raphson method, during the partial fatigue life calculation step in all the elements of the mesh, we create a Matlab interface to identify the critical elements. The strain energy SENER signal of the critical element is corrected to remove the anomalies by a WAFO Matlab interface algorithm. Rainflow cycles are extracted using the Markov formulation in order to calculate the number of signal repetitions to failure, wich is calculated from the Miner law. The results show that the studied loading signal must be repeated 8.86*1011 times before a 25 mm thick aluminium 7075-T6 alloy partruptures.